Subcutaneous Emphysema Caused by an Extraperitoneal Diverticulum Perforation: Description of Two Rare Cases and Review of the Literature - Gael Kuhn; Jean Bruno Lekeufack; Michael Chilcott; Zacharia Mbaidjol (Case Reports in Surgery)
The onset of colon diverticular disease is a frequent event, with a prevalence that increases with age. Amongst possible complications, free peritoneal perforation with abscess formation may occur. We herein describe two rare presentations of an extraperitoneal sigmoid diverticulum perforation. Our first patient, an 89-year-old female with no signs of distress, developed a subcutaneous abscess and emphysema in an incisional hernia following an appendectomy through a McBurney incision. The second patient, an 82-year-old female, was in general distress at the time of her admission and had a more advanced infection following the occurrence of a sigmoid perforation in a hernial sac. Complicated diverticulitis has a known course and evolution, but with an extraperitoneal presentation, this etiology is not expected. A computed tomography (CT) scan should be completed if the patient is hemodynamically stable, and wide debridement should be performed. Subcutaneous emphysema with an acute abdomen may be a sign of sigmoid perforation. Clinicians should keep this etiology in mind, regardless of the initial presentation.